Subconscious vibrotactile stimulation improves mobility and balance in patients with bilateral vestibulopathy: adherence over 2 years - Kingma, Herman; Hougaard, Dan Dupont; van de Berg, Raymond (Frontiers in Neurology, 2024)
Objective To investigate the effect of daily use of subconscious vibrotactile stimulation in bilateral vestibulopathy (BVP) patients, who judged the effect of vestibular rehabilitation as insufficient. Methods BVP patients were asked to wear a subconscious vibrotactile stimulation belt for 2 h. Patients who reported benefit after 2 h of use, were instructed to wear a subconscious vibrotactile stimulation belt in daily life, for up to more than 2 years. Follow-up consultations (mostly by telephone calls) were scheduled after 2 weeks, 2 months, 1 year, and 2 years of use. During these consultations, adherence and the self-reported overall Balance and Mobility Score (BMS) were evaluated. Results One hundred twenty-one BVP patients were included. Regarding adherence, 74% of patients (n = 89) wanted to proceed with daily use at home after 2 h of try out. Of these patients, 90% (n = 80) was still wearing the belt daily after 2 months, and at least 81% (n = 72) after 1 year and 73% (n = 65) after 2 years. It should be noted that lack of adherence after 1 and 2 years resulted from a loss to follow-up. All patients responding to telephone consultations in the 2 years follow up were wearing a subconscious vibrotactile stimulation belt daily. The median BMS score significantly improved within 2 h of use, from 4 to 6 points (p < 0.0001). Compared to baseline, the median BMS score significantly improved with >=3 points after 2 weeks, 2 months, 1 year, and 2 years of daily use (p < 0.0001). Long-term adherence was high in patients who experienced an increase of two or more points on the BMS, after 2 weeks of daily use. Conclusion The Subconscious vibrotactile stimulation improves self-reported balance and mobility in a subgroup of motivated BVP patients in which vestibular rehabilitation is insufficient.